LIVEWORKSHEETS INTERAKTIF SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Argarini, Dian Fitri; Najibah, Daimatun (Universitas Insan Budi Utomo, 2023)
Critical thinking ability is a basic ability that is very important to master, this is because critical thinking is an important component in higher level thinking. Students' low ability to understand mathematical concepts is caused by the use of teaching materials that are less than optimal in applying mathematical concepts. Efforts to overcome the problem of students' low critical thinking abilities require developing teaching materials in the form of Student Activity Sheets (LKS). This is what triggered researchers to carry out research aimed at developing live worksheets to improve students' critical thinking skills at SMP Negeri 1 Sarang. The type of research used is Research and Development (R&D) using the 4D model. The research subjects were class VII junior high school students with data collection instruments in the form of questionnaires, interviews, observations, documentation. The data analysis techniques used in this research are qualitative and quantitative data analysis techniques. The validation results showed that the LKS met the valid criteria with a percentage of 92%. The practical results showed that the LKS met the practical criteria with a percentage of 82.25%. The effectiveness results showed that the LKS met the effective criteria, namely that 80% of students had a score of more than or equal to 75. Based on the research results, it could be concluded that the live worksheet-based LKS to improve students' critical thinking skills in social arithmetic material was valid, practical and effective.